Assessment of serum selenium and ceruloplasmin in potentially malignant disorders and oral cancer - Mathew O Mampilly; Nidhi Ravindran; Mohamed Shajith Parambil; Kumar Nilesh; Parvathi Jayagopalan; Debjit Dhamali (Wolters Kluwer Medknow Publications, 2021)
Introduction: Despite extensive research and development, potentially malignant disorders (PMDs) of the oral cavity and oral cancer remain a serious concern. Diet and immunity have been identified as important modifiable factors in such diseases. Materials and Methods: A total of 20 patients and 10 healthy individuals, aged 30-60 years, were chosen from the outpatient Department of Oral and Maxillofacial Surgery, Yenepoya Dental College and hospital, Karnataka. The participants were grouped into three: Group 1: (10 healthy individuals), Group 2: (10 oral leukoplakia patients) and Group 3: (10 squamous cell carcinoma patients). Blood was chosen as the investigative medium. Ceruloplasmin was estimated by the diamine oxidase method. The technique of atomic absorption developed by Sir Alan Walsh in 1950 has become the preferred method of elemental analysis of selenium (atomic absorption spectrometer). Statistical analysis of the data obtained was done using one-way ANOVA test and the Turkey multiple comparisons test. Results: The intergroup comparison of ceruloplasmin shows that the mean value of Group I (Control) was 31.746 mg/dl, the mean value of Group II (leukoplakia) was 81.411 mg/dl, and the mean value of Group III (squamous cell carcinoma) was 90.7120 mg/dl. The intergroup comparison of selenium levels shows that the mean value of Group I (Control) was 119.937 (ng/ml), the mean value of Group II (leukoplakia) was 109.17 (ng/ml), and the mean value of Group III (squamous cell carcinoma) was 99.6230 (ng/ml). Conclusion: Antioxidants are an important defense system against free radical damage to cells. Ceruloplasmin and selenium levels in serum could be used as disease markers in leukoplakia and squamous cell carcinoma.